Serotype distribution and antibiotic resistance of Streptococcus agalactiae isolated from patients in Hue Central Hospital - Nguyen, Thi Chau Anh; Ung, Thi Thuy; Nguyen, Thi Tuyen; Nguyen, Phi Hung; Vo, Thi Phuong Nhi; Mai, Van Tuan; Le, Van An (Tạp chí Y Dược Huế, 2022)
Group B streptococcus (GBS) infections are still the leading cause of invasive infections in neonates, speci- cally they also seriously cause mortality and morbidity with underlying diseases in adults. Curently, there are ten GBS serotypes (Ia, Ib, and II-IX) and the resistance characteristic of GBS is important to clinical treatment. Objectives and methods : 30 clinical isolates of GBS were obtained from patients in Hue Central Hospital, Vietnam, from January 2016 until Jun 2019. Then the isolated GBS was conducted antimicrobial susceptibility test to determine the antibiotic resistance and serotypes by a multiplex PCR method. Results: GBS strains were resistant to tetracycline (100%), azithromycin (82.6%), erythromycin (80%) and clindamycin (80%). Re- sistance rates were lower with levofloxacin (45%), chloramphenicol (52.6%) and ceftriaxone (6.7%) whereas resistance was not observed in ampicillin, vancomycin and penicillin G. The distribution rate of serotype V (66.67%) was higher than type I (33.33%). Conclusions: Antibiotic resistance characteristics of GBS in samples are mostly familiar with other studies: β -lactams and vancomycin were the most susceptible antibiotics to GBS, the resistance rate in second line drug like clindamycin and erythromycin were high but there were large differences between studies. This study determined two GBS serotypes of Ia and V among isolated strains.